Navigating Challenges of Islamic Civilization in the Era of Global Modernity - Hammis Syafaq; Suqiyah Musafa'ah; Nur Lailatul Musyafaah; Marli Candra; Andina Najma Shavia (Tasfiyah: Jurnal Pemikiran Islam, 2026)
This article analyzes the dynamics and challenges faced by Islamic civilization amid the dominance of Western modernity, which has now transformed into neoliberal globalization, digital capitalism, and epistemic hegemony. The study explores how Islamic civilization can reformulate its strategic role in constructing a modern Muslim society that is not only technologically advanced but also spiritually and ethically grounded. Employing a qualitative library-based method with a descriptive-analytical approach and a civilizational analytical framework, this research examines classical and contemporary literature on civilizational theory, modernization, the coloniality of knowledge, and Islamic reformism. The findings indicate that Western modernity does not merely generate scientific and institutional progress; it also promotes a secular-materialistic paradigm that tends to marginalize the dimension of transcendence from the public sphere. In this context, the crisis experienced by Muslim societies is not a theological crisis, but rather an epistemic one crisis and a crisis of civilizational confidence. Historically, Islamic civilization was built upon the integration of dzikr (spiritual consciousness) and fikr (intellectual rationality) as two fundamental pillars of societal advancement. Therefore, the revitalization of Islamic civilization in the global era requires the reconstruction of epistemology, educational reform, and the strengthening of a civilizational identity that engages modernity in a selective and critical manner.